Consumption Time of Captopril Influenced the Outcomes of Patients with Stage 1 Hypertension - Sulastri Herdaningsih; Ahmad Muhtadi; Keri Lestari (Universitas Padjadjaran, 2017)
Differences in drugs consumption time may affect its absorption and metabolism in the body which could lead to differences in its efficacy. For hypertension patients, one of the most frequently used drugs for lowering blood is captopril. However, information regarding the influence of consumption time on captopril efficacy was limited. Therefore, this study was conducted to compare the efficacy of captopril in lowering blood pressure when administered before and after meal. This was an experimental study with two treatment groups, conducted at Dr. Soedarso General Hospital, Pontianak, Indonesia, during April-June 2015. Statistical analysis was performed using Mann-Whitney, Exact-Fisher, and T-test. We found out that the reduction of systolic blood pressure in group who consumed captopril before and after meal was 30 mmHg and 25 mmHg, respectively (p<0.05). The similar reduction in diastolic bloos pressure was observed in both groups (10 mmHg, p>0.05). In conclusion, it is recommended to take captopril on an empty stomach since it showed better efficacy when administered before meal compared to after meal consumption. Keywords: hypertension, captopril, absorption